2022
DOI: 10.3390/microorganisms10030572
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Characterization of Melon-Headed Whales (Peponocephala electra) Stranded in China

Abstract: Although gut microbes are regarded as a significant component of many mammals and play a very important role, there is a paucity of knowledge around marine mammal gut microbes, which may be due to sampling difficulties. Moreover, to date, there are very few, if any, reports on the gut microbes of melon-headed whales. In this study, we opportunistically collected fecal samples from eight stranded melon-headed whales (Peponocephala electra) in China. Using high-throughput sequencing technology of partial 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This is quite distinct from the microbial information of the Risso’s dolphin stranded in Korea waters, which was predominately Photobacterium (89.4%) (Kim et al 2019 ). The Risso’s dolphin shared common gut microbial members associated with Firmicutes with a wide range of toothed whales, including the Chinese white dolphin ( Sousa chinensis ) (Wan et al 2021 ), Yangtze finless porpoise ( N. a. asiaeorientalis ) (Wan et al 2016 ), bottlenose dolphin ( Tursiops truncatus ) (Wan et al 2022 ), melon-headed whales ( Peponocephala electra ) (Bai et al 2022 ), short-finned pilot whales ( Globicephala macrorhynchus ) (Bai et al 2021 ), pygmy ( Kogia breviceps ), and dwarf ( K. sima ) sperm whales (Erwin et al 2017 ), whereas at the genus level, the Risso’s dolphin diverged from other toothed whales. For example, unlike Halomonas , Photobacterium , and Cetobacterium , detected as abundant taxa in the marine dolphins and porpoises (Wan et al 2018 , 2021 , 2022 ), the Risso’s dolphin contained higher proportions of Vagococcus (5.94%) and Bacteroides (4.27%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is quite distinct from the microbial information of the Risso’s dolphin stranded in Korea waters, which was predominately Photobacterium (89.4%) (Kim et al 2019 ). The Risso’s dolphin shared common gut microbial members associated with Firmicutes with a wide range of toothed whales, including the Chinese white dolphin ( Sousa chinensis ) (Wan et al 2021 ), Yangtze finless porpoise ( N. a. asiaeorientalis ) (Wan et al 2016 ), bottlenose dolphin ( Tursiops truncatus ) (Wan et al 2022 ), melon-headed whales ( Peponocephala electra ) (Bai et al 2022 ), short-finned pilot whales ( Globicephala macrorhynchus ) (Bai et al 2021 ), pygmy ( Kogia breviceps ), and dwarf ( K. sima ) sperm whales (Erwin et al 2017 ), whereas at the genus level, the Risso’s dolphin diverged from other toothed whales. For example, unlike Halomonas , Photobacterium , and Cetobacterium , detected as abundant taxa in the marine dolphins and porpoises (Wan et al 2018 , 2021 , 2022 ), the Risso’s dolphin contained higher proportions of Vagococcus (5.94%) and Bacteroides (4.27%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was found that C. somerae was able to promote the expression of insulin in zebrafish to lower blood glucose, and C. somerae was also able to activate the parasympathetic nervous system through the metabolite acetic acid, which promotes the expression of insulin and the ability of glucose utilization of fish and plays an important role in regulating the health of the fish [45]. Clostridium sensu stricto 1 is a common group in the gut microbial community of freshwater fish [10], but it is also frequently found in the gut of marine mammals [46][47][48], where it often appears as a potential pathogen [49,50]. Bacteria of the genus Romboutsia are Gram-positive bacteria, one of the common intestinal microorganisms, and most species of Romboutsia originate from the gut, although some isolated strains of Romboutsia have originated from diseased individuals, but recent reports have shown that this group of bacteria contains a polysaccharide-synthesizing enzyme that produces (1,3;1,4)-β-d-glucans, so the role of this group of bacteria in the human and mammalian gastrointestinal tract is less clear [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus is another potentially detrimental group of bacteria, but it has not been directly related to pathogenesis in marine mammals; it has been found in the oral cavity and intestine of the Yangtze finless porpoise ( Neophocaena asiaeorientalis ) ( 51 ) and sperm whales ( Physeter catodon ) ( 52 ). Enterococcus has been reported to be among the dominant fecal bacteria of captive or stranded but not diseased cetaceans ( 42 , 52 56 ). In the present study, whether detrimental or not, the considerable decrease of Shigella (from 35.2% to 4.4%), Escherichia (from 5.5% to 0.7%), and Streptococcus (from 17.1% to 0.1%) in the second period after metronidazole admission reduced any potential risks from these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Of similar abundance was the genus Bacteroides whose abundance increased from 0.1% to 5.3% between the first and second periods. This genus has been found in the oral ( 51 ) and fecal ( 53 , 54 , 70 ) microbiome of cetaceans. In humans, it is considered one of the commensal bacteria that first colonize the gut after vaginal birth ( 71 ), and this could be also the case for the M. monachus pups.…”
Section: Discussionmentioning
confidence: 99%